Hybrid Aerogels: Graphene Hybrid Aerogels Made via Phase Transfer Strategy (Adv. Mater. Interfaces 22/2016). Issue 22 (November 2016) - Sun, Rui; Li, Guangyong; He, Weina; Wang, Jin; Song, Qijun; Zhang, Xuetong
Abstract : Phase transfer method with graphene oxide as surfactant to synthesize graphene hybrid aerogels is firstly demonstrated by Xuetong Zhang, Rui Sun, and co‐workers in article 1600541. The incorporated nanomaterials range from metal, metal oxide to polymer nanostructures with different shape and size. Enhanced surface‐enhanced Raman spectro‐scopy performance is manifested by rGO‐Ag NWs hybrid aerogel due to the host‐guest interaction enhancement.